Long-Term Habituation of the Gill-Withdrawal Reflex in Aplysia Requires Gene Transcription, Calcineurin and L-Type Voltage-Gated Calcium Channels - Esdin, Joseph; Pearce, Kaycey; Glanzman, David L. (Frontiers in Behavioral Neuroscience, 2010)
Although habituation is possibly the simplest form of learning, we still do not fully understand the neurobiological basis of habituation in any organism. To advance the goal of a comprehensive understanding of habituation, we have studied long-term habituation (LTH) of the gill-withdrawal reflex (GWR) in the marine snail Aplysia californica. Previously, we showed that habituation of the GWR in a reduced preparation lasts for up to 12 h, and depends on protein synthesis, as well as activation of protein phosphatases 1 and 2A and postsynaptic glutamate receptors. Here, we have used the reduced preparation to further analyze the mechanisms of LTH in Aplysia. We found that LTH of the GWR depends on RNA synthesis because it was blocked by both the irreversible transcriptional inhibitor actinomycin-D and the reversible transcriptional inhibitor, 5,6-dichlorobenzimidazole riboside (DRB). In addition, LTH requires activation of protein phosphatase 2B (calcineurin), because it was disrupted by ascomycin. Finally, LTH was blocked by nitrendipine, which indicates that activation of l-type voltage-gated Ca2+ channels is required for this form of learning. Together with our previous results, the present results indicate that exclusively presynaptic mechanisms, although possibly sufficient for short-term habituation, are insufficient for LTH. Rather, LTH must involve postsynaptic, as well as presynaptic, mechanisms.